2020
DOI: 10.21203/rs.3.rs-49481/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Medical Students: A Multicenter Quantitative Study

Abstract: Background: The COVID-19 pandemic disrupted the United States (US) medical education system with the necessary, yet unprecedented Association of American Medical Colleges (AAMC) national recommendation to pause all student clinical rotations with in-person patient care. This study is a quantitative analysis investigating the educational and psychological effects of the pandemic on US medical students and their reactions to the AAMC recommendation in order to inform medical education policy.Methods: The authors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 11 publications
4
23
0
Order By: Relevance
“…On the other hand, most students reported that the pandemic affected their normal medical educations and daily lives. These sudden shocks may cause an increased risk of mental health symptoms (Harries et al., 2021). Due to the nursing profession's specificity, most of the students in our school of nursing were female, so only 13.2% of the respondents included in this study were male.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most students reported that the pandemic affected their normal medical educations and daily lives. These sudden shocks may cause an increased risk of mental health symptoms (Harries et al., 2021). Due to the nursing profession's specificity, most of the students in our school of nursing were female, so only 13.2% of the respondents included in this study were male.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 741 medical students across the USA evaluated students' anxiety with a 7-point Likert scale. There was a statistically significant increase in self-reported emotional exhaustion and burnout from before the pandemic and since the pandemic started (p < 0.001) [7]. Additionally, medical students from Idaho expressed 'a lot' or 'extreme' concern regarding the toll COVID-19 will take on public health (64%), the economy (61%), the health of loved ones (61%), and not knowing when the pandemic would end (59%) [11].…”
Section: Covid-19 Mental Health Impactmentioning
confidence: 99%
“…On 17 March 2020, the Association of American Medical Colleges (AAMC) recommended all medical schools to pause all student clinical rotations with inperson patient care. A US study surveying a total of 741 medical students found that most students (74.7%) believed that the pandemic had significantly disrupted their medical education and 61.3% believed that they should continue with normal clinical rotations during the pandemic [7]. 83.4% students were willing to accept the risk of infection with COVID-19 if they had to return to the clinical setting [7].…”
Section: Impact Of Covid-19 Curriculum Changesmentioning
confidence: 99%
“…And similar views were expressed in a study conducted among medical students. [27] Crowded accomodation facility and lack of cleanliness in hostels of government medical colleges as well as more patient burden in hospital might be the crucial reasons of difference. [28] Conclusion COVID-19 pandemic has imposed enormous challenges on medical education worldwide.…”
Section: Discussionmentioning
confidence: 99%